Genetic architecture of orbital telorism. Issue 9 (15th November 2021) - Knol, Maria J; Pawlak, Mikolaj A; Lamballais, Sander; Terzikhan, Natalie; Hofer, Edith; Xiong, Ziyi; Klaver, Caroline C W; Pirpamer, Lukas; Vernooij, Meike W; Ikram, M Arfan; Schmidt, Reinhold; Kayser, Manfred; et al.
Abstract: The interocular distance, or orbital telorism, is a distinctive craniofacial trait that also serves as a clinically informative measure. While its extremes, hypo- and hypertelorism, have been linked to monogenic disorders and are often syndromic, little is known about the genetic determinants of interocular distance within the general population. We derived orbital telorism measures from cranial magnetic resonance imaging by calculating the distance between the eyeballs' centre of gravity, which showed a good reproducibility with an intraclass correlation coefficient of 0.991 (95% confidence interval 0.985–0.994). Heritability estimates were 76% (standard error = 12%) with a family-based method (N = 364) and 39% (standard error = 2.4%) with a single nucleotide polymorphism-based method (N = 34 130) and were unaffected by adjustment for height (model II) and intracranial volume (model III) or head width (model IV). Genome-wide association studies in 34 130 European individuals identified 56 significantly associated genomic loci ( P < 5 × 10 −8 ) across four different models of which 46 were novel for facial morphology, and overall these findings replicated in an independent sample ( N = 10 115) with telorism-related horizontal facial distance measures. Genes located nearby these 56 identified genetic loci were 4.9-fold enriched for Mendelian hypotelorism and hypertelorism genes, underlining their biological relevance. This study provides novel insights into the genetic architecture underlying interocular distance in particular, and the face in general, and explores its potential for applications in a clinical setting.